The Effectiveness of Crossword Puzzle Games toward the Students Vocabulary Achievement at VII Grade in SMPN 1 Nangaroro - Yustinus Tegu; Munawwir Hadiwijaya (ANFA MEDIATAMA, 2022)
The study about the effectiveness of Crossword Puzzle Games toward the Students Vocabulary at seventh grade in SMPN I Nangaroro in the academic year 2019/2020. The objective of this research is to find out the effectiveness or not using crossword puzzle games toward Students' vocabulary achievement in seventh grade in SMPN I Nangaroro. The sample of this research was seventh-grade students of SMPN I Nangaroro. They were VII-C as the experimental class which consists of 20 students. For the sampling technique, the researcher used purposive sampling. In getting the data, the researcher used pre-test and post-test. The instrument of this research was the test. In analyzing the data, the researcher used the T-test formula for analyzing The result of this study showed students' pre-test means score in the experimental class was 53.5 while the post-test mean score was 76.5. The result of the statistical calculation, the hypothesis of this research used T-table at a significant level of 0.05. According to the T-table list, the value of the distribution table 19 as a degree of freedom was 1.05. However, in this research T-score (TO) is 4.30 and T-table is 1.05. It is known that T-score is bigger than T-table = 4.30 > 1.05. Based on the result concluded Alternative Hypothesis (Ha) was accepted and the Null Hypothesis (Ho) was rejected. The finding of the study using crossword puzzle games in learning vocabulary is an effective way and quite a success it can improve the students' achievement in learning vocabulary.